Three‐Dimensional Simulations of Ultra‐Relativistic Electron Acceleration During the 21 April 2017 Storm. Issue 4 (6th April 2023) - Guo, Deyu; Xiang, Zheng; Ni, Binbin; Jin, Taifeng; Zhou, Ruoxian; Yi, Juan; Liu, Yangxizi; Dong, Junhu
Abstract: The acceleration mechanisms of ultra‐relativistic electrons (>∼5 MeV) have received more and more attention in the Van Allen Probes era. Both chorus waves and radial diffusion are considered capable of accelerating ultra‐relativistic electrons, and their roles in acceleration still under debate today. In this study, we present 3‐D simulations for evaluating the evolutions of ultra‐relativistic electron phase space density (PSD) during a weak storm on April 2017. Comparison of simulation results with observations suggests that local peaks in PSD profile of ultra‐relativistic electrons are generated by chorus waves, then smoothed and widened due to the transport of electrons from the peak to either side by radial diffusion. Chorus waves act dominantly in the acceleration of ultra‐relativistic electrons while radial diffusion assists. We also found that radial diffusion coefficient model of W. Liu et al. (2016, https://doi.org/10.1002/2015GL067398 ) is more suitable and reasonable than model of Brautigam and Albert (2000, https://doi.org/10.1029/1999JA900344 ) for 3‐D simulation of ultra‐relativistic electrons. A more accurate radial diffusion coefficient model is vital and demanded for quantitatively evaluating the contribution of these two mechanisms for ultra‐relativistic electrons acceleration in the future. Key Points: Acceleration process of ultra‐relativistic electrons during the April 2017 storm are simulated using a three‐dimensional simulation model Chorus waves play significant roles in accelerating ultra‐relativistic electron while radial diffusion assists, forming local phase space density peaks Different radial diffusion coefficient models have great effects on the simulation results of ultra‐relativistic electrons